Economic Load Analysis of Smoker and Non- Smoker Fisherman in Medan City - Aulia, Destanul; Ayu, Sri Fajar (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2021)
Urban fisherman have low to medium economic income. Limited income for fisherman becomes an economic burden. Fisherman consume cigarettes to the point of addiction, and thus do not prioritize family needs. The research objective was to analyze the economic burden of urban fisherman and compare the economic burden between smoker and non-smoker fisherman. The respondents were 50 smoker fisherman and 50 non-smoker fisherman in Medan Belawan. The research method uses the t test to see the difference in the economic burden of smoker and non-smoker fisherman. The results showed 76% of smoking fisherman believed that smoking was harmful to health. There is a significant difference between the economic burden between smoking and nonsmoking . The economic expense for a smoker is 42.8% or IDR846,400 of your monthly income. However, only 8% of fisherman have health complaints due to smoking. Smokers' priority places cigarettes in second place after basic needs. It is recommended that the government not stop providing knowledge about the evils of smoking to fisherman and stop the entry of cigarettes in fishing areas so it can reduce the economic burden on low-income people.